Association between Yogurt Consumption and Intestinal Microbiota in Healthy Young Adults Differs by Host Gender - Suzuki, Yoshio; Ikeda, Keiichi; Sakuma, Kazuhiko; Kawai, Sachio; Sawaki, Keisuke; Asahara, Takashi; Takahashi, Takuya; Tsuji, Hirokazu; Nomoto, Koji; Nagpal, Ravinder; Wang, Chongxin; Nagata, Satoru; et al. (Frontiers in Microbiology, 2017)
Human intestinal microbiota are influenced by various factors viz. diet, environment, age, gender, geographical and socioeconomic situation, etc. among which diet has the most profound impact. However, studies investigating this impact have mostly included subjects from diverse geographic/ socioeconomic backgrounds and hence the precise effects of dietary factors on gut microbiota composition remain largely confounded. Herein, with an aim to evaluate the association between dietary habits, specifically yoghurt consumption, and the gut microbiota in healthy young adults sharing similar age, lifestyle routine, geographical setting, etc., we conducted a cross-sectional study wherein 293 collegiate freshmen answered a questionnaire about their frequency of yoghurt consumption over the last 2 months and provided stool specimens for microbiota analysis. Fecal microbiota were analyzed by highly sensitive reverse-transcription-quantitative-PCR assays targeting bacterial 16S rRNA molecules. Fecal organic acids were measured by HPLC. Overall, the gut microbiota were predominated (97.1±8.6%) by Clostridium coccoides group, Clostridium leptum subgroup, Bacteroides fragilis group, Bifidobacterium and Atopobium cluster. Interestingly, after adjusting the data for yoghurt consumption, females were found to have higher total bacterial (P=0.013) and Bifidobacterium (P=0.046) count and fecal pH (P=0.007) and lower fecal concentration of total organic acids (P=0.030), succinic acid (P=0.007) and formic acid (P=0.046) as compared to males. Altogether, yoghurt consumption showed positive linear association with Lactobacillus and L. gasseri subgroup in both male and female subjects; however, several gender-specific disparities were also detected in this yoghurt-microbiota association. Yoghurt consumption demonstrated a negative association with L. sakei subgroup, Enterobacteriaceae and Staphylococcus in males but shared a positive association with L. casei subgroup and succinic acid in female subjects. The study manifests the association between yoghurt consumption and gut microbiota in a healthy homogeneous cohort and show how this association can differ by host gender. The findings should be helpful for prospective studies investigating the diet-microbiome interaction in human health and disease.